Economic of different alternative livelihood projects in Southern Municipalities of Iloilo - Besana, Nikkei Mesa
The study aims to determine and analyze the economics of different alternative livelihood projects in southern municipalities of Iloilo, namely Tigbauan, Miag-ao and San Joaquin.